Topography of the 410-km discontinuity from PP and SS precursors - Chambers, K; Woodhouse, J; Deuss, A (2005)
A number of previous studies have confirmed the global existence of a transition zone discontinuity at 410-km depth by aligning large numbers of long-period seismograms on a surface reflection phase before stacking. Discussion of SS and PP precursors from the 410-km discontinuity (termed P410P and S410S) has largely focused on the long-wavelength topography of this discontinuity. Recent models suggest that the precursor derived topography of the 410-km discontinuity is dominated by low degree spherical harmonics. However, there remain some discrepancies as to the details of the topography and its relation to mantle processes. Here we present a new model for 410-topography which is constrained using both P410P and S410S measurements, and examine the relationship between our observations of 410 topography and seismic velocity anomalies in the transition zone. We find a moderate negative correlation between discontinuity topography and transition zone seismic velocity anomalies at very low spherical harmonic degrees. This is consistent with the expected relationships between, the position of the α-β olivine phase boundary, seismic velocity anomalies, and mantle temperatures. However, when shorter wavelengths are included the relationship becomes more complex. In smaller regions beneath Northeast Asia and the Western Pacific we observe positive correlations between seismic velocities and discontinuity topography, which we interpret as evidence for the effects of chemical heterogeneities on seismic velocities and the 410-km discontinuity. Our results suggest there is a long wavelength temperature pattern in the mantle, however at shorter wavelengths the influence of chemical heterogeneities becomes visible in seismic velocity anomalies and mantle discontinuity topography. This separation of the spectra for thermal and chemical heterogeneities suggests that short wavelength chemical heterogeneities can survive in convecting mantle. © 2005 Elsevier B.V. All rights reserved.